2015
DOI: 10.1371/journal.pone.0139671
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Immune Response to DNA Vaccine Encoding Bacillus anthracis PA-D4 Protects Mice against Anthrax Spore Challenge

Abstract: Anthrax has long been considered the most probable bioweapon-induced disease. The protective antigen (PA) of Bacillus anthracis plays a crucial role in the pathogenesis of anthrax. In the current study, we evaluated the efficiency of a genetic vaccination with the fourth domain (D4) of PA, which is responsible for initial binding of the anthrax toxin to the cellular receptor. The eukaryotic expression vector was designed with the immunoglobulin M (IgM) signal sequence encoding for PA-D4, which contains codon-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Besides antigen optimization, we also employed an optimized DNA vaccine vector carrying a transcriptional enhancer that was able to strengthen the antigen production and therefore immune response of DNA vaccine. Recently our studies revealed that inclusion of the tandem repeat sequence of SV 40 enhancer upstream of a promoter in the plasmid vector enhanced the antibody production as much as 10-fold [19]. Following immunization with IgM-tL1R through electroporation, we observed the induction of a prominent antibody response.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Besides antigen optimization, we also employed an optimized DNA vaccine vector carrying a transcriptional enhancer that was able to strengthen the antigen production and therefore immune response of DNA vaccine. Recently our studies revealed that inclusion of the tandem repeat sequence of SV 40 enhancer upstream of a promoter in the plasmid vector enhanced the antibody production as much as 10-fold [19]. Following immunization with IgM-tL1R through electroporation, we observed the induction of a prominent antibody response.…”
Section: Discussionmentioning
confidence: 71%
“…The HRPconjugated goat-anti mouse IgG was added to each well as a secondary antibody and incubated for 1 h at 37°C. The antibody titers were determined using an end-point dilution ELISA titration assay described before [19].…”
Section: Elisa For Measuring Serum Antibodymentioning
confidence: 99%
See 1 more Smart Citation
“…strain BPS_CRB 12 revealed the maximum antimicrobial activity beside S. aureus and E. coli, which was supported by Munoz-Atienza et al (2013), who stated that 20% of the bacteria have antimicrobial activity against three of the eight tested bacterial pathogens. Bacillus anthracis strain BPS_CRB14 exhibited significant antimicrobial activity (Haber and Ilan, 2013, Crawford et al, 2009, Kim et al, 2015, Addae et al, 2014, Athamna et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…38 The SV40 enhancer increases nuclear uptake, particularly in non-dividing cells, 39 increases transgene expression 40 and potentiates the antibody response. 41 The F protein, a type 1 viral protein, has long been considered the most promising target for developing DNA vaccine candidates against HRSV due to its conserved nature and its ability to activate both the humoral and cellular immune responses. 42 However, the use of the non-optimized F gene in DNA vaccination has provided unsatisfactory protection in The heatmaps were generated using the MORPHEUS software tool.…”
Section: Discussionmentioning
confidence: 99%